2013
DOI: 10.3389/fonc.2013.00206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prognostic Value of Two Common Variants of BRCA1 and BRCA2 Genes in Ovarian Cancer Patients Treated with Cisplatin and Paclitaxel: A Gynecologic Oncology Group Study

Abstract: Purpose: BRCA1/BRCA2 germline mutations appear to enhance the platinum-sensitivity, but little is known about the prognostic relevance of polymorphisms in BRCA1/BRCA2 in epithelial ovarian cancer (EOC). This study evaluated whether common variants of BRCA1/BRCA2 are associated with progression-free survival (PFS) and overall survival (OS) in patients with advanced stage sporadic EOC.Experimental Design: The allelic frequency of BRCA1 (2612C > T, P871L-rs799917) and BRCA2 (114A > C, N372H-rs144848) were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Similar results have also been reported by the studies conducted on the Brazilian Family Health program where a low performance score in family focus, community orientation and accessibility was reported [10,12,26,27]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results have also been reported by the studies conducted on the Brazilian Family Health program where a low performance score in family focus, community orientation and accessibility was reported [10,12,26,27]. …”
Section: Discussionsupporting
confidence: 89%
“…The results of this analysis carried out in six localities in Bogotá confirmed the preliminary results of the pilot assessment in one locality of the city [ 17 ], which found that the lowest rated dimensions were family focus, community orientation, accessibility and financial resources distribution . Similar results have also been reported by the studies conducted on the Brazilian Family Health program where a low performance score in family focus, community orientation and accessibility was reported [ 10 , 12 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Though no functional researches have been performed to date, it is credible to say that this amino acid substitution can alter protein function to some degree [21]. Since the discovery of the BRCA1 rs799917 polymorphism, besides breast cancer, it has been widely researched in ovarian cancer [36], cervical cancer [37], non-small cell lung cancer [38], esophageal squamous cell carcinoma [39] and even nonHodgkin lymphoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…When assessed for response to therapy, p.Pro871Leu showed no association with either advanced phases of CML or treatment response (Gutierrez-Malacatt et al, 2016). The CT/TT genotypes have been reported to be associated with ovarian cancer progression in non-African American patients, but not with progression-free survival (PFS) and overall survival (OS) in patients treated with cisplatin and paclitaxel (Tian et al, 2013). The TT genotype has been reported to not only contribute to increased breast cancer risk associated with combined estrogen monotherapy in postmenopausal women in Germany (Abbas et al, 2010), but also with recurrence of TNBC after radiotherapy in Han Chinese (Shi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%